Ancaman Kemanan Jaringan Wi-fi (Nethercap) - M. Ziran, Syarifudin, Sebastian Rinaldi, Irfan Zulkarnaen (Integrative Perspectives of Social and Science Journal, 2025)
Wi-Fi networks are a crucial infrastructure that supports digital connectivity across various sectors. However, despite their convenience, Wi-Fi networks are vulnerable to numerous cyberattacks, including those conducted using Nethercap, a tool capable of launching man-in-the-middle attacks, packet sniffing, SSID spoofing (Evil Twin), and login page manipulation (captive portal phishing). This study aims to identify the characteristics of Nethercap attacks, assess their impact on data security, and explore mitigation strategies to reduce the risk of data breaches. The research method employed is a literature study, analyzing a wide range of academic sources, security standards, and recent technical reports relevant to the topic. The findings indicate that Nethercap exploits poorly encrypted Wi-Fi protocols, weak user authentication, and a general lack of user awareness regarding rogue network threats. Therefore, securing Wi-Fi networks requires a comprehensive approach involving advanced technologies (such as WPA3, WIDS, and SIEM), strict security policies, and continuous user security education.